Kodifikasi Hukum Keluarga Islam di Negara Tunisia dan Yordania - ali hamdan (Al Maqashidi : Jurnal Hukum Islam Nusantara, 2024)
Marriage is a form of worship so there needs to be rules that are able to maintain the existence of a marriage, as in Islamic marriages in various Muslim countries in the world, including the Muslim countries of Tunisia and Jordan, where these countries are two of several other countries that support the rules. in marriage, as an effort carried out by the two countries, namely by reforming and codifying Islamic family law. There are several reforms to marriage regulations that have been implemented, including registration of marriages, where both countries require registration of marriages, such as Tunisia, which states that marriages that are not registered are punished as invalid. Likewise, Jordan, which is slightly different, apart from being illegal, will also be fined, this applies to prospective brides (men and women) as well as officers who do not register the marriage. Apart from the regulations above, the two countries also updated the minimum age limits for marriage, polygamy and procedures for implementing divorce. Apart from that, the research method used by the author is Library Research, which is a data collection technique by reviewing various literature, such as journals, books, scientific works, the internet, etc. Meanwhile, the data analysis technique uses descriptive analytical methods. By looking at several of these regulatory updates, of course the state has thought about the aim of the marriage law reform, which is none other than protecting the rights of married couples, discrimination against child marriage, children's rights, and mental health in carrying out domestic relationships.